Determinants and rates of retention in HIV care among adolescents receiving antiretroviral therapy in Windhoek, Namibia: a baseline cohort analysis - Farai K. Munyayi; Brian E. van Wyk (BMC, 2023)
Abstract Background Long-term engagement in HIV care is essential to achieving and maintaining viral suppression. Adolescents living with HIV (ALHIV) experience many barriers to remaining engaged in care and treatment programs. Higher attrition among adolescents compared to adults remains a huge concern due to unique psychosocial and health systems challenges adolescents face, and recently the COVID-19 pandemic effects. We report on determinants and rates of retention in care in adolescents aged 10-19 years enrolled on antiretroviral therapy (ART) in Windhoek, Namibia. Methods A retrospective cohort analysis of routine clinical data of 695 adolescents aged 10-19 years enrolled for ART at 13 Windhoek district public healthcare facilities, between January 2019 and December 2021 was conducted. Anonymized patient data were extracted from an electronic database and registers. Bivariate and Cox proportional hazards analysis were performed to determine factors associated with retention in care among ALHIV at 6, 12, 18, 24 and 36 months. Retention in care trends were also described using the Kaplan-Meier survival analysis. Results The retention in care rates at 6, 12, 18, 24 and 36 months were 97.7%, 94.1%, 92.4%, 90.2%, and 84.6%, respectively. Our study population had predominantly treatment-experienced adolescents, who initiated ART between birth and 9 years (73.5%), were on treatment for > 24 months (85.0%), and on first-line ART (93.1%). After controlling for confounders, the risk of dropping out of care was increased for older adolescents aged 15-19 years (aHR = 1.964, 95% CI 1.033-3.735); adolescents on switched ART regimens (Second line + Third line regimen) (aHR = 4.024, 95% CI 2.021-8.012); adolescents who initiated ART at 15-19 years (aHR = 2.179, 95%CI 1.100-4.316); and male adolescents receiving ART at a PHC clinic (aHR = 4.322, 1.332-14.024). Conversely, the risk of ALHIV dropping out of care decreased for adolescents whose TB screen results were negative (aHR = 0.215, 95% CI 0.095-0.489). Conclusion Retention in care rates among ALHIV in Windhoek do not meet the UNAIDS revised target of 95%. Gender-specific interventions are needed to keep male and older adolescents motivated and engaged in long-term care, and to promote adherence amongst those adolescents who were initiated on ART in late adolescence (15-19 years).